The Evil of Refraining to Save: Liu on the Doctrine of Doing and Allowing - Blair, Jacob (Diametros, 2017)
In a recent article, Xiaofei Liu seeks to defend, from the standpoint of consequentialism, the Doctrine of Doing and Allowing: DDA. While there are various conceptions of DDA, Liu understands it as the view that it is more difficult to justify doing harm than allowing harm. Liu argues that a typical harm doing involves the production of one more evil and one less good than a typical harm allowing. Thus, prima facie, it takes a greater amount of good to justify doing a certain harm than it does to justify allowing that same harm. In this reply, I argue that Liu fails to show, from within a consequentialist framework, that there is an asymmetry between the evils produced by doing and allowing harm. I conclude with some brief remarks on what may establish such an asymmetry.